Problems of formation and establishment of the united territorial communities boundaries: land-legal aspects - Dorosh, Y.; Kupriyanchyk, I.; Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2019)
As a result of the research, it was found that the lack of formed and established boundaries in newly formed territorial communities significantly affects the implementation of land management within their territory, the reliability of land registration and statistical reporting, the flow of funds to local budgets, the efficiency and rationality of the use of natural resources, which complicates the activities of local self-government bodies. It was clarified that the implementation of projects for the formation and establishment of boundaries of village and settlement councils was not carried out, that is, the formation of their boundaries took place only on paper without verification on the ground, and as a result, inaccurate areas and limits were obtained. These measures may be introducedin case of implementation of the proposed changes to the Land Code of Ukraine and the Law of Ukraine "On Land Management". The expected results are presented in the event of implementation of these measures.Key words: united territorial community, formation of boundaries, establishment of boundaries, bodies of local self-government.